Association between Statin Use and Gastric Cancer: A Nested Case-Control Study Using a National Health Screening Cohort in Korea - Mi Jung Kwon; Ho Suk Kang; Joo-Hee Kim; Ji Hee Kim; Se Hoon Kim; Nan Young Kim; Eun Sook Nam; Kyueng-Whan Min; Hyo Geun Choi (MDPI AG, 2021)
Concerns about the hazards of statins on the development and mortality of stomach cancers remain controversial. Here, we investigated the likelihood of incident gastric cancers and related mortality depending on statin exposure, statin type, and the duration of use. This nested case-control-designed study was composed of 8798 patients who were diagnosed with gastric cancer and matched with 35,192 controls at a 1:4 ratio based on propensity scores of age, sex, residential area, and income from the Korean National Health Insurance Service-Health Screening Cohort database (2002-2015). Propensity score overlap weighting was adjusted to balance the baseline covariates. Overlap propensity score-weighted logistic regression analyses were assessed to determine associations of the prior use of statins (any statin, hydrophilic statins vs. lipophilic statins) with incident gastric cancer and its mortality depending on the medication duration (<180 days, 180-545 days, and >545 days) after adjusting for multiple covariates. After adjustment, the use of any statin, hydrophilic statins, or lipophilic statins showed significant associations with lower odds for incident stomach cancer when used for a short-term period (180-545 days) (OR = 0.88, 95% CI = 0.81-0.86, p = 0.002; OR = 0.78, 95% CI = 0.66-0.92, p = 0.004; and OR = 0.91, 95% CI = 0.84-0.99, p = 0.039, respectively) compared to the control group. Hydrophilic statin use for 180-545 days was associated with 53% lower overall mortality (OR = 0.47; 95% CI = 0.29-0.77). In subgroup analyses, beneficial effects on both cancer development and mortality persisted in patients ≥65 years old, patients with normal blood pressure, and patients with high fasting glucose levels. There were no such associations with long-term statin use (>545 days). Thus, the current nationwide cohort study suggests that prior short-term statin use may have anti-gastric cancer benefits in elderly patients with hyperglycemia.